Pengembangan Briket Batok Kelapa di Desa Billapora Rebba: Inovasi Berbasis Sumber Daya Lokal - Mohammad Syarief; Riski Riski; Siti Mufrokhatin Nikmah; Dewi Solehatin; Faninazila Azzahra Amnurdiant (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Strengthening local potential is a concept to create independent and prosperous villages. One supporting initiative is utilizing coconut shell waste into charcoal briquettes. Indonesia is the world's largest coconut producer. One such area is Billapora Rebba Village, Lenteng Subdistrict, Sumenep Regency, though this potential remains unoptimized. Collective community awareness and bureaucratic support are needed to build micro-enterprise ecosystems or home-scale utilization benefiting society. This awareness can be initiated through Kuliah Kerja Nyata (KKN) activities. The purpose of this writing is to manifest or document a widely and periodically accessible record in journal article form. The research method is Asset-Based Community Development (ABCD), a community development approach. Results show coconut shell waste can be turned into briquettes, as demonstrated by simulations and socialization